USING HOMOPHONE GAMES TO IMPROVE PRONUNCIATION FOR HIGH SCHOOL STUDENT - Harsin Harsin; Rifiqoh Rifiqoh; Mashuri Mashuri (Tadulako University, 2022)
The objective of this research is to prove that the use of homophone games can improve pronunciation of the eleventh grade students at SMKN 1 Sojol. This research applied pre-experimental research design. The sample of this research was 21 eleventh grade students of ATPH 1 (Agribisnis Tanaman Pangan dan Horticultura) as known as Agriculture major, consisting of 21 students. The sample was selected by using a purposive sampling technique. The data were collected by administering a pronunciation test conducted before and after treatment, called pre-test and post-test. The result of pre-test and post-test shows that the mean score of pre-test is 34.44, and the mean score of post-test is 76.19. The result of data is analyzed statically by applying t-test formula. The result of data analysis shows that the value of the t-counted is(4.30) was higher than the t-table value (1.725) by applying 0.05 level of significance and 20 degree of freedom (df) 21-1 =20. The implication of this finding is to the betterment of teaching pronunciation is that the teacher needs to use Homophone Games to improve students’ pronunciation.